Normalisation of blood pressure in hypertensive TGR(mREN2)27 rats by amlodipine vs. enalapril: effects on cardiac hypertrophy and signal transduction pathways - Witte, Klaus; Huser, Lutz; Knotter, Bianca; Heckmann, Markus; Schiffer, Sabine; Lemmer, Björn (Naunyn-Schmiedeberg's archives of pharmacology, 2001)
It is still a controversial issue whether different classes of antihypertensive drugs are equally effective in the regression of cardiac hypertrophy and associated complications. The present study compared the effects of prolonged treatment with the Ca2+-channel blocker amlodipine and the ACE inhibitor enalapril, respectively, in TGR(mREN2)27 rats (TGR), an animal model of renin-dependent hypertension.
Published online: 26 October 2000
Gesehen am 11.04.2022